ENERGY EFFICIENCY OF DIFFERENT WAYS OF CENTRAL HEATING - A. E. Piir; V. B. Kuntysh; A. Yu. Vereshchagin (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The article shows the calculation comparison of fuel for producing of heat-line water with a help of different technological installations, transforming (converting) high-grade heat from burning process of fuel or in the process of non-reversible heat exchange with coolant (heating agent), or with a help of heat engines, which allow to decrease losses of working efficiency and thus to reduce the use of fuel. There were considered five types of plants beginning from the  simplest  one  up  to  the  most  complex  in  two  variants,  when  the  heat  exchangers and machines are perfect (ideal) and when equipment has the known degree of efficiency (perfection):1) water-heat boiler station, working on organic fuel;2) electrical boiler station, obtaining energy on power transmission lines from condensing power station;3) line heater of TPP, obtaining steam from heating turbine;4) line heater CPP, powered by steam from pressure reducing unit;5) heat pump, producing energy on power supply lines from TPP.In this article were investigated three ideal reversible ways of transformation of   high- grade heat into low-grade heat with a help of decreasing and increasing and combined (suggested by the authors) heat transformers and their thermodynamic equivalence was shown in this article. And there were suggested universal installation for electric energy generation, cold and heat of two grades for heat-water supply and the heating process on the base of gascompressors   gas turbines. These results are so important (actual) for power engineers of the countries with  increasing consumption  of organic  fuel and  its enhancement in  value and realizing programs of energy saving .The analysis shows, that the quality of produced low-grade heat per unit of used high-grade heat for ideal plants (installations) is: electrical boiler unit – 0.7;  water boiler unit – 1.0; for heat pump, heating turbine, combined heat transformers   – 4.9. Increasing of quality of high-grade heat does not break the Law of Thermodynamics, just on the contrary, thank this the constant heat efficiency is remained. Conversion ratio for real variants of these plants are: 0.415; 0.9; 1.53; 2.8; 1.47. Thus, it is once more proved, that TPP is the most efficient source of heat for heating process and stands head above electrical boiler unit in 7 times, above plants with heat pumps in 2 times. Universal electric power plant is comparable in effi- ciency with heat pump system, but outperforms it due to its multi-functionality.